Design, synthesis, and antitumor activity evaluation of carbazole derivatives with potent HDAC inhibitory activity - Sun, Likun; Han, Leiqiang; Zhang, Liang; Chen, Chen; Zheng, Chengyun (Medicinal chemistry research, 2023)
Histone deacetylase (HDAC), a key regulator in controlling the acetylation status of histone, are considered to be associated with viability, migration, invasion, proliferation and apoptosis of malignant tumors. The HDAC inhibition is an effective strategy for designing compounds against malignant tumors and five compounds have been approved by FDA or NMPA for clinical therapy. In this study, we designed and synthesized a series of novel carbazole-hydroxamate analogues as HDAC inhibitors and evaluated their anti-tumor properties in vitro. Compared with vorinostat, the HDAC semi-inhibitory concentration of compounds 3f and 3g decreased 4–13 folds, compounds 8a and 8c also showed strong inhibitory HDAC activity, and compound 3g had a strong inhibitory effect on HDAC 1. The CCK8 assay showed that compounds 3g displayed good antiproliferative activity on tested tumor cells. Flow cytometric and western blot assay showed that 3g exerted anti-tumor activities by regulating the level of Ac-HH3 and activating the cleaved caspase 3. Based on these results, carbazole-hydroxamate derivative 3g might become a potential anti-tumor candidate molecule to further structural optimization research. Graphical Abstract